Purification and biochemical characterization of a novel β-fructofuranosidase from Penicillium oxalicum with transfructosylating activity producing neokestose. Issue 8 (August 2015) - Xu, Qiangsheng; Zheng, Xiaoqun; Huang, Meiping; Wu, Min; Yan, Yusi; Pan, Jiamao; Yang, Qi; Duan, Cheng-Jie; Liu, Jun-Liang; Feng, Jia-Xun
Graphical abstract